Mitochondrial Targeting in Photodynamic Therapy. Metabolic and Drug Structure Requirements for Specific Mitochondrial Localization. A Pilot Investigation - (:unkn) unknown (My University, 2012)
Photodynamic therapy (PTD) has shown promise in the treatment of certain types of cancer (Davis et al. 1985, Chen 1988). One appealing strategy under consideration to selectively target tumor cells in PDT is that of mitochondrial targeting (Chen 1988, Chen 1989). The concept of mitochondrial targeting has its origin in the pioneering observation by Chen and colleagues that an enhanced mitochondrial transmembrane potential (ΔΨmito) is a prevalent tumor cell phenotype (Davis et al. 1985, Chen 1988). Because the plasma transmembrane potential is negative on the inner side of the cell, and the mitochondrial transmembrane potential is negative on the matrix side of this organelle, a variety of extensively conjugated cationinc molecules (i.e., cationic dyes) tend to accumulate in energized cell mitochondria with a high degree of specificity. In keeping with the larger transmembrane potentials typically observed in tumor cells, a number of cationic dyes were already found both to accumulate in larger quantities and be retained for longer periods in the mitochondria of these cells as compared to normal cells (Chen 1988, Chen 1989). In these last cases, the respective (photo) toxic effects observed toward tumor cells were considerably higher than the effects observed toward normal cells (Belostotsky et al. 2011). Thus, a differential in dye loading and retention, when observed between normal and tumor cells, can provide an opportunity for the selective destruction of the latter cells via mitochondrial targeting. The rational development of novel PDT agents for mitochondrial targeting is currently limited by the lack of a reliable model describing how the molecular structure of cationic dyes control the degree of specificity with which these agents localize in energized cell mitochondria, and may preferably accumulate in tumor cells as compared to normal cells. Likewise, the reasons why mitochondrial transmembrane potentials are typically higher in tumor cells are yet to be understood. The objectives of this project were two-fold. First, to investigate how the molecular structure and charge in a series of rhodamine dyes affects their subcellular distribution/mitochondrial localization. Second, to explore whether mitochondrial transmembrane potentials may be affected by enhanced glutaminolysis when the supply of glucose is limited. To this end, we have used a non-transformed cell line (CV-1, African green monkey kidney cells) as a biological model. Glutaminolysis is an anaplerotic pathway thought to be highly active in tumor cells. Our findings have provided further evidence which support previous inferences on the structural requirements for rapid and selective mitochondrial localization. First, the PDT agent must be a cationic species at physiological pH. Zwitterionic species do not show these desirable properties. Second, cationic dyes showing lipophilic character similar to that of the prototypical mitochondrial marker Rhodamine-123 can be expected to localize in energized cell mitochondria with a high degree of specificity, although such specificity is presumably lost when the lipophilic character of the cationic agent is significantly higher than that of Rhodamine-123. These studies have also indicated that the mitochondrial transmembrane potentials of CV-1 cells apparently increase when these cells experience glucose starvation and derive their energy needs primarily from glutamine/glutaminolysis. The observed effects were modest though, and very severe morphological abnormalities were simultaneously noticed. Although these results appear to represent the first line of evidence on the possibility that the enhanced mitochondrial potential typically observed in tumor cells may (at least in part) be a result of enhanced glutaminolysis, further investigations will be required in order to better explore such possibility. In addition, while the development of a single cell model for use in studies dealing with mitochondrial targeting would be highly desirable, e.g., CV-1 cultures showing either high or normal mitochondrial potentials as modulated by the characteristics of the growth media, the morphological abnormalities observed in this study (for cells grown under conditions of glucose starvation) may represent a major limitation for the development of such a biological model.